1980
DOI: 10.1080/15298668091425301
|View full text |Cite
|
Sign up to set email alerts
|

Animal toxicity studies with ammonium perfluorooctanoate

Abstract: These studies were conducted to evaluate the potential toxicity of ammonium perfluorooctanoate, a commercial surfactant. They include acute and subchronic feeding studies with rabbits, mice, rats and monkeys as well as in vitro mutagenicity assays with Salmonella typhimurium and Saccharomyces cerevisiae. The compound was non-irritating to the skin and moderately irritating to the eyes of rabbits. The rat oral LD50 was 540 mg/kg; no deaths resulted from a one hour rat inhalation exposure at a nominal concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 0 publications
2
59
0
Order By: Relevance
“…PFAAs are known to affect the liver, causing hypertrophy and in some cases necrosis, in rodents (Chengelis et al, 2009;Goldenthal, 1978;Griffith and Long, 1980;Kawashima et al, 1995;Kennedy, 1987;Lieder et al, 2009b;Mertens et al, 2010;van Otterdijk, 2007avan Otterdijk, , 2007bZhang et al, 2008). Hepatocyte hypertrophy was observed at as low as 0.064~0.23 mg/kg/day in a 2-year dietary study of PFOS (Thomford, 2002) and 0.64 mg/kg/day in a 13-week dietary study of PFOA (Perkins et al, 2004) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…PFAAs are known to affect the liver, causing hypertrophy and in some cases necrosis, in rodents (Chengelis et al, 2009;Goldenthal, 1978;Griffith and Long, 1980;Kawashima et al, 1995;Kennedy, 1987;Lieder et al, 2009b;Mertens et al, 2010;van Otterdijk, 2007avan Otterdijk, , 2007bZhang et al, 2008). Hepatocyte hypertrophy was observed at as low as 0.064~0.23 mg/kg/day in a 2-year dietary study of PFOS (Thomford, 2002) and 0.64 mg/kg/day in a 13-week dietary study of PFOA (Perkins et al, 2004) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, Oat2 expression is not gender-predominant in mouse kidney. Interestingly, perfluoro-octanoic acid (PFOA), a chemical used in the production of nonstick cookware and protective finishes on carpets, is excreted into urine by female rats at a greater rate than by male rats (Griffith and Long, 1980;Hanhijärvi et al, 1982;Kudo et al, 2002). Additionally, PFOA induces liver toxicity in male rats, but not in female rats, presumably due to differences in the urinary excretion rate (Griffith and Long, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PAH, renal clearance of PFOA is greater in female than male rats (Griffith and Long, 1980;Hanhijärvi et al, 1982;Kudo et al, 2002). Griffith and Long (1980) demonstrated that male rats developed hepatotoxicity at lower PFOA treatment levels than did females, and corresponding serum levels were 75-226 fold greater in males than in females.…”
Section: Fig 3 Effects Of Hx and Gh Treatments On Oat Mrna In Kidnementioning
confidence: 99%
“…Griffith and Long (1980) demonstrated that male rats developed hepatotoxicity at lower PFOA treatment levels than did females, and corresponding serum levels were 75-226 fold greater in males than in females. These differences were attributed to relatively slow urinary excretion in male as compared with female rats, and led to the conclusion that female rats possess an active secretory mechanism which is lacking or inactive in male rats (Hanhijärvi et al, 1982).…”
Section: Fig 3 Effects Of Hx and Gh Treatments On Oat Mrna In Kidnementioning
confidence: 99%